Behavior of eccentrically loaded UHPC filled circular steel tubular short columns. (June 2022) - Wang, Qiuwei; Liang, Lin; Lui, Eric M.; Shi, Qingxuan
Abstract: This paper presents experimental results of twelve eccentrically loaded short composite columns made by filling circular steel tubes with ultra-high performance concrete (UHPC) cured under room temperature. Using these test data as benchmarks, finite element models are developed and used to perform parametric studies to determine how the capacities of these columns are affected by load eccentricity and tube diameter-to-thickness ratio. In addition, a relationship between the balanced eccentricity ratio and the confinement coefficient is established. The results of the present study have shown that: (1) failure of these columns is characterized by yielding of the steel tubes, followed immediately by failure of the core concrete; (2) a decrease in diameter-to-thickness ratio increases the peak load and improves the column's post-peak behavior; (3) an increase in the load eccentricity ratio results in a reduction of the load capacity, ductility and stiffness of the column; (4) the compressive strain in the steel tube develops more rapidly due to second-order effect, and the assumption that plane sections remain plane no longer applies when the applied load reaches 80% of the peak load. By comparing the axial force – Bending moment ( N u - M u ) interaction diagrams generated in the present study with existing codes, it is found that the code equations are mostly conservative. A set of trilinear N u - M u interaction equations that can produce more accurate results is therefore proposed Highlights: Twelve short composite columns subjected to eccentric loads were tested. Ultra-high performance concrete cured under room temperature was used. Finite element models were developed to conduct parametric studies. Axial load-bending moment interaction diagrams were generated. A new set of triaxial interaction equations was proposed.